Repositioning fusidic acid for tuberculosis: semi-synthesis of analogues and impact of mycobacterial biotransformation on antibiotic activity - Wasuna, Antonina (Department of Chemistry, 2018)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is one of the leading causes of death globally, especially in low and middle-income countries. TB is primarily a curable disease, with chemotherapy predicated on a combination of four drugs. The increase in multiple forms of drug-resistant TB is a major cause for concern, underpinning the importance of a continuous pipeline of new anti-TB agents. Drug repositioning - that is, the optimization of existing drugs for new therapeutic indications - has shown promise in expanding the therapeutic options for TB chemotherapy. Fusidic acid (FA), a natural product-derived antibiotic, has modest in vitro antimycobacterial activity. Through a multi-disciplinary approach combining aspects of chemistry and biology, this study investigated the pharmacological and physicochemical properties of FA that might be exploited for optimization of FA as a lead compound for TB drug discovery. FA is a weak carboxylic acid, and it was hypothesised that the carboxylic acid moiety limits its permeation of the complex mycobacterial cell wall. Therefore, this study aimed to identify novel FA analogues with improved permeation properties and designed to act as potential prodrugs. By modifying the C-3 hydroxyl and the carboxylic acid moiety, alkyl and aminoquinoline derivatives were covalently fused to FA through ester and amide coupling reactions to generate hybrids and/or potential prodrugs.